MODELING THE SUSTAINABILITY OF PRIVATE MEDICAL SCHEMES IN A REGULATED ENVIRONMENT - Owen, Craig Sean (My University, 2011)
The costs of healthcare insurance continue to rise year-on-year far in excess of general inflation. The response to this global phenomenon has often been to increasingly regulate the healthcare insurance industry or the private medical scheme industry as it is known in South Africa. This research models the sustainability of the private medical scheme industry in South Africa in an increasingly regulated environment. Two techniques are employed, namely the Delphi technique, using the opinions of industry experts, and mathematical modeling using Fuzzy Cognitive Mapping (FCM). The principal findings of this report are that the current plethora of regulations are creating an unstable, unsustainable industry that is not only becoming increasingly unaffordable but is also indirectly discriminating against those members of society that the regulations are designed to assist. The report also comments on specific policy aspects contained within the Medical Schemes Act of 1998 (Republic of South Africa, 1998) and other official documents that should be reviewed in a co-operative fashion by government and industry stakeholders
MBA thesis - WBS
Keywords: Medical aid schemes; Healthcare insurance